SYNERGY BETWEEN LEGISLATORS AND ACADEMICS FOR THE ECONOMIC SELF-RELIANCE OF PEMATANG JOHAR - Nasution, Edwin Sugesti; Moktar, Brilian; Kanchanawongpaisan, Sipnarong; Sartiyah, Sartiyah; Khun, Loo Teck; Abd.Rashid, Muhammad Hafiz; Kurniawan, Rendi (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: This community service activity aims to strengthen village economic self-reliance through synergy between legislators and academics in Pematang Johar Village, Deli Serdang Regency. The program was designed using a participatory and educational approach that integrates academic perspectives and public policy to enhance community capacity in entrepreneurship, economic awareness, and understanding of policy support for village economic development. The implementation methods included lectures and interactive discussions focusing on local potential-based business development, community participation in economic activities, and the role of legislators in supporting village economic empowerment. Evaluation was conducted using pre- and post-activity questionnaires to assess changes in participants’ understanding, attitudes, and motivation. The results indicate significant improvements across all evaluation indicators, including understanding of village economic self-reliance, awareness of community and legislative roles, entrepreneurial knowledge, self-confidence, and motivation to engage in sustainable economic activities. The findings demonstrate that synergy between academics and legislators provides added value in community empowerment by combining knowledge transfer with policy perspectives. Overall, this community service activity contributes to strengthening community capacity, collective awareness, and social capital as foundations for sustainable village economic self-reliance. Keywords: community service; village economic self-reliance; community empowerment; legislators; academics Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat kemandirian ekonomi desa melalui sinergi antara legislator dan akademisi di Desa Pematang Johar, Kabupaten Deli Serdang. Kegiatan dirancang menggunakan pendekatan edukatif dan partisipatif yang mengintegrasikan perspektif akademik dan kebijakan publik untuk meningkatkan kapasitas masyarakat dalam kewirausahaan, kesadaran ekonomi, serta pemahaman terhadap peran kebijakan dalam pengembangan ekonomi desa. Metode pelaksanaan meliputi ceramah dan diskusi interaktif yang berfokus pada pengembangan usaha berbasis potensi lokal, partisipasi masyarakat dalam kegiatan ekonomi, serta peran legislator dalam mendukung pemberdayaan ekonomi desa. Evaluasi kegiatan dilakukan melalui kuesioner sebelum dan sesudah kegiatan untuk mengukur perubahan pemahaman, sikap, dan motivasi peserta. Hasil evaluasi menunjukkan adanya peningkatan yang signifikan pada seluruh indikator, termasuk pemahaman tentang kemandirian ekonomi desa, peran masyarakat dan legislator, pengetahuan kewirausahaan, kepercayaan diri, serta motivasi untuk mengembangkan usaha secara berkelanjutan. Hasil kegiatan ini menunjukkan bahwa sinergi antara akademisi dan legislator memberikan nilai tambah dalam proses pemberdayaan masyarakat melalui penguatan kapasitas dan perspektif kebijakan. Secara keseluruhan, kegiatan pengabdian ini berkontribusi dalam membangun kapasitas masyarakat, kesadaran kolektif, dan modal sosial sebagai fondasi kemandirian ekonomi desa yang berkelanjutan. Kata kunci: pengabdian kepada masyarakat, kemandirian ekonomi desa, pemberdayaan masyarakat, legislator, akademisi